White asphalt mixture for highway tunnel pavement as well as preparation method and application of white asphalt mixture

By developing a white asphalt mixture containing bright asphalt, coarse aggregate, fine aggregate, titanium dioxide, mineral powder and composite flame retardant, the problems of insufficient light environment in the tunnel and the stability of asphalt pavement are solved, and the effects of improving the brightness in the tunnel, reducing traffic accidents and improving the fire resistance of the pavement are achieved.

CN119912195AActive Publication Date: 2025-05-02SHAANXI EXPRESSWAY ENG TESTING INSPECTION & TESTING CO LTD

Patent Information

Application Number
CN202411894097.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-05-02
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The insufficient light environment in the tunnel leads to poor driving sight, increasing the frequency of traffic accidents, and the prior art will affect the stability and durability of asphalt pavement when adding flame retardants.

Method used

A white asphalt mixture for road surfaces is developed, containing bright asphalt, coarse aggregate, fine aggregate, titanium dioxide, mineral powder and composite flame retardant. Through specific ratios and preparation methods, the reflectivity, flame retardant performance and durability of the road surface are improved.

Benefits of technology

It improves the brightness in the tunnel, improves the driver's visual environment, reduces the probability of traffic accidents, and improves the fire resistance and durability of asphalt pavement by adding composite flame retardants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201286980000141
    Figure BDA0005201286980000141
Patent Text Reader

Abstract

The invention provides a white asphalt mixture for a highway tunnel pavement as well as a preparation method and application of the white asphalt mixture. The white asphalt mixture comprises the following components in parts by weight: 4-7 parts of bright asphalt, 50-58 parts of coarse aggregate, 25-30 parts of fine aggregate, 1-3 parts of titanium dioxide, 2-4 parts of mineral powder and 2.5-3.5 parts of a composite flame retardant, the composite flame retardant comprises nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of (50-52): (30-35): (8-10). The white asphalt mixture for the road tunnel pavement provided by the invention is applied to pavement of the road tunnel pavement. And the flame-retardant and smoke-suppression performance of the mixed asphalt pavement is improved, and meanwhile, the high-temperature and low-temperature stability of the pavement is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road engineering materials, and in particular to a white asphalt mixture for highway tunnel pavement, and a preparation method and application thereof. Background Art

[0002] With the rapid increase in the mileage of China's highway construction, the number and mileage of tunnels are also increasing sharply. At the same time, the frequent safety accidents in tunnels have also touched the pain points of highway managers and technicians. The reason is that on the one hand, the poor driving visibility due to insufficient lighting in the tunnel makes the tunnel an accident-prone section, which seriously affects the driving safety in the tunnel. This situation is particularly obvious in short tunnels without lighting conditions; on the other hand, the frequency of traffic accidents in the entrance and exit sections of the tunnel is significantly higher than that in the middle section of the tunnel. This is because the tunnel light environment is composed of the light environment outside the tunnel and the lighting environment inside the tunnel. The brightness outside the tunnel is usually much higher than the brightness inside the tunnel. When the driver enters or exits the tunnel, the drastic changes in light and dark can easily make it difficult for the driver's vision to adapt in time, causing the "black hole effect" and "white hole effect". These adverse effects of the tunnel light environment will reduce the driver's visual efficacy, increase the driver's visual burden, and even cause the driver's visual illusion, which will induce tunnel traffic accidents, seriously affecting the driving safety of the tunnel, reducing driving comfort and energy-saving effects. Therefore, it is of great significance to study how to improve the light environment of tunnels, improve the visual environment of drivers when driving in tunnels, and improve the safety of driving in tunnels.

[0003] In order to improve the efficiency of tunnel lighting, improve the visual environment of drivers in tunnels, and improve driving safety, the project intends to develop a high-performance white asphalt mixture from the perspective of high-brightness asphalt pavement paving, and lay it in the tunnel pavement to form a high-brightness "white asphalt pavement", which can solve the following problems: When applied to the internal pavement of the tunnel, especially the short tunnel under no lighting conditions, because the reflectivity of the white pavement is higher than the original black asphalt pavement, when the lights of the moving motor vehicles shine on the pavement, it can achieve the effect of increasing the brightness inside the tunnel, thereby improving the driving comfort of the driver inside the tunnel; when applied to the entrance and exit of the tunnel, the strong reflectivity of the white asphalt pavement can reduce the brightness difference between the entrance and exit of the tunnel, thereby reducing the visual blind spots formed by the driver when entering and exiting the tunnel, and improving the driver's driving safety inside the tunnel.

[0004] In addition, in special sections of tunnels, once a fire occurs, ordinary asphalt pavement is easily ignited and the fire spreads rapidly. At present, during the construction of tunnel asphalt pavement, flame retardants are usually added to asphalt to reduce the fire hazard in the tunnel, reduce the flammability of the asphalt pavement or even make it self-extinguishing, significantly reduce the possibility of fire, and reduce casualties and property losses caused by asphalt combustion. However, in the prior art, when adding flame retardants, various additives will have a slight impact on each other. Although the purpose of flame retardancy of the asphalt pavement is achieved, it will have some negative impact on the road performance of the asphalt pavement, such as causing the stability and durability of the asphalt pavement to decrease. Summary of the invention

[0005] The present application provides a white asphalt mixture for highway tunnel pavement and a preparation method and application thereof, in order to solve the above-mentioned problems mentioned in the background technology.

[0006] The present application provides a white asphalt mixture for a highway tunnel pavement, the white asphalt mixture comprising, by weight: 4-7 parts by weight of bright asphalt, 50-58 parts by weight of coarse aggregate, 25-30 parts by weight of fine aggregate, 1-3 parts by weight of titanium dioxide, 2-4 parts by weight of mineral powder and 2.5-3.5 parts by weight of a composite flame retardant;

[0007] The composite flame retardant comprises nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of (50-52):(30-35):(8-10) respectively.

[0008] Optionally, the bright asphalt includes the following components: 30-33.3 parts by weight of cyclohexane oil, 62-66.7 parts by weight of petroleum resin, 5-8 parts by weight of EVA resin, 4-33 parts by weight of SBS modifier, 1-1.5 parts by weight of compatibilizer and 2-22 parts by weight of anti-aging agent.

[0009] Optionally, the anti-aging agent includes 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:2-5.5:0.2-0.4.

[0010] Optionally, the particle size of the coarse aggregate is classified into 5-10 mm crushed stone and 10-15 mm crushed stone, wherein the weight ratio of 5-10 mm crushed stone to 10-15 mm crushed stone is 40-43:20-25.

[0011] Optionally, the particle size of the fine aggregate is classified into 0-3 mm machine-made sand and 3-5 mm crushed stone, wherein the weight ratio of 0-3 mm machine-made sand to 3-5 mm crushed stone is 26-29:5-9.

[0012] Optionally, the titanium dioxide is selected from anatase titanium dioxide and rutile titanium dioxide.

[0013] Optionally, the petroleum resin is one or more of C9 petroleum resin, C5 petroleum resin or coumarone resin.

[0014] On the other hand, the present application provides a method for preparing a white asphalt mixture for a highway tunnel pavement, the method being used to prepare the above-mentioned white asphalt mixture, the method comprising the following steps:

[0015] (1) Heat the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively according to weight;

[0016] (2) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, fine aggregate and bright asphalt heated in the above step (1) into the preheated container, and stirring at a speed of 45-75 r / min for 50-60 s to obtain a mixture A;

[0017] (3) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0018] (4) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 120-150 min to obtain a white asphalt mixture.

[0019] Optionally, the method for preparing bright color asphalt comprises the following steps:

[0020] Mixing and preheating step: taking naphthenic oil, petroleum resin and EVA resin by weight, and stirring and preheating at 160-170°C for 10-25min to obtain a molten mixture, and the stirring speed is 700-1000rad / min;

[0021] SBS modifier and compatibilizer adding step: maintaining the temperature at 160-170° C., adding the SBS modifier and compatibilizer to the molten mixture, and shearing at a speed of 4500-5500 rad / min for 30-35 minutes;

[0022] Anti-aging agent adding step: cooling to 150-160°C, and adding 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in sequence, shearing at a speed of 2000-2500 rad / min for 15-20 minutes to obtain a bright-colored asphalt primary product;

[0023] Development steps: Place the initial bright-colored asphalt product in an oven at 160-165°C for 1.5-2 hours to obtain bright-colored asphalt.

[0024] On the other hand, the present application provides an application of a white asphalt mixture for a highway tunnel pavement in the paving of a highway tunnel pavement. The white asphalt mixture is the above-mentioned white asphalt mixture, or a white asphalt mixture prepared by the above-mentioned method.

[0025] The white asphalt mixture for highway tunnel pavement and the preparation method and application thereof provided in the present application realize the preparation of the white asphalt mixture for highway tunnel pavement, and have the following beneficial effects compared with the prior art:

[0026] (1) By adding composite flame retardants to white asphalt mixtures, the combustion performance of asphalt pavement can be effectively improved, the spread of fire can be prevented, and the damage to the pavement caused by fire can be reduced, thereby improving the fire resistance of the pavement. At the same time, it has a certain smoke suppression effect, reducing the emission of harmful smoke when a fire occurs, thereby reducing harm to personnel. By compounding nanoclay, ammonium polyphosphate and aluminum hydroxide in a special weight ratio, and synergistically acting from different flame retardant mechanisms, the flame retardant and smoke suppression performance of white asphalt mixtures can be improved. In addition, the nanoclay in the flame retardant is dispersed in the bright asphalt, filling the gaps between the asphalt and the coarse aggregate and fine aggregate, thereby increasing the density of the white asphalt mixture, thereby promoting the bearing capacity and compressive strength of the pavement. Aluminum hydroxide has a certain alkalinity. After compounding with ammonium polyphosphate, it can better interact and mix with the acidic bright asphalt, improve the uniformity of the asphalt mixture, prevent the agglomeration of components in the asphalt mixture, and thereby improve the uniformity and durability of the pavement. The present application not only achieves the flame retardant and smoke suppression properties of the white asphalt mixture by adding a composite flame retardant in a special proportion, but also has a good promoting effect on the compressive strength, bearing capacity and durability of the asphalt mixture.

[0027] (2) By adding magnesium silicate to the composite flame retardant, the nanoclay is a modified nanoclay obtained by modification with N-hydroxyoctanoylamide. The nanoclay is modified with N-hydroxyoctanoylamide to increase the interlayer distance of the nanoclay, and N-hydroxyoctanoyl is grafted on the surface and interlayer of the thin layer of nanoclay. Compared with the nanoclay, the surface area is increased, and the surface adsorption capacity is also increased. At the same time, the synergistic effect with ammonium polyphosphate and aluminum hydroxide is enhanced, the flame retardant and smoke suppression performance of the road surface is improved, and the describing properties between the components are improved, so that the dispersion performance of the nanoclay in the asphalt mixture is improved. At the same time, the modification of N-hydroxyoctanoyl forms a three-dimensional network structure between the modified nanoclay and the components in the asphalt mixture, which improves the high temperature stability and bearing capacity of the asphalt mixture, thereby improving the road performance of the asphalt mixture. Magnesium silicate is also adsorbed between the layers and on the surface of the modified nanoclay, further filling the pores between the modified nanoclay and asphalt, improving the stability of the three-dimensional network structure, thereby improving the integrity of the mixed asphalt pavement and further improving the flame retardant and smoke suppression properties.

[0028] (3) By paving the white asphalt mixture provided by the present application on the road tunnel pavement, not only the reflection intensity of the road tunnel pavement to light is increased, the light environment of the tunnel is improved, and the safety of tunnel driving is improved. At the same time, the purpose of flame retardancy and smoke suppression of the tunnel road is achieved. More importantly, the high temperature stability and durability of the tunnel road pavement are further improved, and the road performance of the pavement is improved. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0030] The present application provides a white asphalt mixture for a highway tunnel pavement, the white asphalt mixture comprising, by weight: 4-7 parts by weight of bright asphalt, 50-58 parts by weight of coarse aggregate, 25-30 parts by weight of fine aggregate, 1-3 parts by weight of titanium dioxide, 2-4 parts by weight of mineral powder and 2.5-3.5 parts by weight of a composite flame retardant;

[0031] The composite flame retardant comprises nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of (50-52):(30-35):(8-10) respectively.

[0032] Specifically, mixing bright asphalt with other components can firmly bond the various components in the mixture together to form an overall structure, thereby enhancing the mechanical properties and durability of the mixture. At the same time, bright asphalt can fill the gaps between aggregates, reduce the porosity of the mixture, and improve the density and impermeability of the white asphalt mixture, thereby enhancing the durability and road performance of the pavement. Coarse aggregate mainly plays a skeleton role in the asphalt mixture, providing greater bearing capacity and wear resistance for the asphalt mixture, thereby enhancing the bearing capacity and stability of the road, thereby extending the service life of the road. Fine aggregate fills the gaps between coarse aggregates, improves the density and stability of the asphalt mixture, thereby enhancing the durability and waterproof performance of the road. By compounding coarse aggregates and fine aggregates with different particle sizes, the strength of the asphalt mixture is jointly improved, and the bearing capacity and stability of the pavement are improved. On the one hand, titanium dioxide acts as a whitening agent to improve the whiteness and glossiness of asphalt mixture, making the asphalt mixture appear white when laid on the road surface. On the other hand, titanium dioxide has a certain ultraviolet absorption capacity, which slows down the aging process of asphalt mixture and thus extends the service life of the road surface.

[0033] Preferably, the coarse aggregate and the fine aggregate are light-colored stones, that is, white or grayish white stones, which include at least one of silica, granite, dolomitic limestone, dolomite, white quartz, white marble, and white rain flower stone. While ensuring the color, the key indicators of the crushing value and polishing value of the coarse aggregate and the fine aggregate should meet the relevant requirements of JTGF40-2004 "Technical Specifications for Highway Asphalt Pavement Construction", which are not particularly limited here.

[0034] Mineral powder has a large surface area, which is conducive to the formation of structural asphalt. The greater the proportion of structural asphalt, the higher the cohesion of the asphalt mixture. Therefore, adding an appropriate amount of mineral powder can significantly improve the cohesion of the asphalt mixture, and can improve the physical and chemical adsorption capacity of the asphalt mixture, reduce the generation of free asphalt, increase the proportion of structural asphalt, thereby improving the cohesion and waterproof performance of the mixture. At the same time, mineral powder can play a filling role in the asphalt mixture, reduce the pores in the asphalt mixture, increase the density, and further improve the stability and waterproofness of the road surface.

[0035] Preferably, the mineral powder is a lighter-colored limestone mineral powder, such as white or off-white, and has an alkali value of 0.97, which can be more evenly mixed with acidic light-colored asphalt to enhance the adhesion of the asphalt mixture, thereby improving the density, stability and compressive strength of the road surface. Preferably, the particle size of the mineral powder is 0.02-0.075 mm.

[0036] By adding composite flame retardants to white asphalt mixtures, the combustion performance of asphalt pavement can be effectively improved, the spread of fire can be prevented, and the damage to the pavement caused by fire can be reduced, thereby improving the fire resistance of the pavement. At the same time, it has a certain smoke suppression effect, reducing the release of harmful smoke when a fire occurs, thereby reducing harm to personnel. Among them, nanoclay has a layered structure, which can form a physical barrier to prevent the spread of flames and effectively prevent the spread of flames. At the same time, the layered structure and surface hydrophilicity of nanoclay cause it to produce chemical reactions and release water at high temperatures, forming a vacuum effect, preventing the diffusion of air, oxygen and combustion products, thereby preventing the spread of flames. Ammonium polyphosphate has the advantages of high efficiency flame retardancy and environmental friendliness. Aluminum hydroxide decomposes when heated and absorbs a large amount of heat, thereby reducing the temperature of the material surface and achieving the purpose of delaying combustion.

[0037] By compounding nanoclay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of (50-52): (30-35): (8-10), the three work synergistically to improve the flame retardant and smoke suppression properties of white asphalt mixture from different flame retardant mechanisms. At the same time, the nanoclay in the flame retardant is dispersed in the bright asphalt, filling the gaps between the asphalt and the coarse aggregate and fine aggregate, thereby increasing the density of the white asphalt mixture, and thus promoting the bearing capacity and stability of the pavement. Aluminum hydroxide has a certain alkalinity. After compounding with ammonium polyphosphate, it can better interact and mix with the acidic bright asphalt, improve the uniformity of the asphalt mixture, prevent the agglomeration of components in the asphalt mixture, and thus improve the uniformity and durability of the pavement. The present application not only achieves the flame retardant and smoke suppression properties of the white asphalt mixture by adding a special proportion of composite flame retardant, but also has a good promoting effect on the compressive strength, bearing capacity and durability of the asphalt mixture. Preferably, the particle size of the nanoclay is 1-100nm.

[0038] Optionally, the bright asphalt includes the following components: 30-33.3 parts by weight of cyclohexane oil, 62-66.7 parts by weight of petroleum resin, 5-8 parts by weight of EVA resin, 4-33 parts by weight of SBS modifier, 1-1.5 parts by weight of compatibilizer and 2-22 parts by weight of anti-aging agent.

[0039] Specifically, naphthenic oil and petroleum resin are used as the main components of light-colored asphalt, and the naphthenic oil and petroleum resin are modified by EVA resin and SBS modifier. The modification of EVA resin can improve the high-temperature strength and stability of asphalt mixture, reduce rutting and permanent deformation, and the modification of SBS can improve the adhesion and elasticity of asphalt mixture, improve the adhesion and bonding force between light-colored asphalt and other component materials, thereby improving the compressive strength and anti-stripping performance of asphalt mixture. The compatibilizer can improve the compatibility between naphthenic oil, petroleum resin and EVA resin and SBS modifier by means of the bonding force between molecules, so that the mixed system maintains good stability during the modification process, promotes the modification of naphthenic oil and petroleum resin, and then improves the bearing capacity and stability of light-colored asphalt.

[0040] Preferably, the compatibilizer is furfural extracted oil, which can improve the compatibility of various components in the bright asphalt.

[0041] Optionally, the anti-aging agent includes 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:2-5.5:0.2-0.4.

[0042] Specifically, the anti-aging agent reacts with the active ingredients in the light-colored asphalt to form a protective film, which prevents the erosion of asphalt by factors such as ultraviolet rays, oxidation and temperature. The formed protective film can delay the aging process of asphalt, maintain the softness and elasticity of asphalt, and thus reduce cracking and damage to the road surface. The 1076 antioxidant can promote the antioxidant properties of light-colored asphalt. LDHs is a layered dihydroxy complex metal hydroxide, which can shield the inorganic layer from ultraviolet light and greatly reduce the excitation effect of ultraviolet light in the process of photo-oxidative aging of asphalt. The nitrogen atoms in tallow amine polyoxyethylene ether react with the active ingredients in the light-colored asphalt. At the same time, tallow amine polyoxyethylene ether can cooperate with 1076 antioxidant and LDHs with micelles to better disperse in the light-colored asphalt, improve the stability of the protective film, and form an isolation barrier, thereby reducing the damage of ultraviolet rays, oxygen, etc. to the light-colored asphalt and delaying the aging time of the road surface.

[0043] Optionally, the particle size of the coarse aggregate is classified into 5-10 mm crushed stone and 10-15 mm crushed stone, wherein the weight ratio of 5-10 mm crushed stone to 10-15 mm crushed stone is 40-43:20-25.

[0044] Optionally, the particle size of the fine aggregate is classified into 0-3 mm machine-made sand and 3-5 mm crushed stone, wherein the weight ratio of 0-3 mm machine-made sand to 3-5 mm crushed stone is 26-29:5-9.

[0045] Specifically, by compounding coarse aggregate and fine aggregate of different particle size classifications, the fine aggregate can fill the pores between the coarse aggregate and asphalt, improve the density and stability of the asphalt mixture, and thus improve the durability of the road surface.

[0046] Optionally, the titanium dioxide is selected from anatase titanium dioxide and rutile titanium dioxide.

[0047] Specifically, the particle size of titanium dioxide is selected to be between 120-350nm. Titanium dioxide has a suitable surface area, which helps to achieve uniform mixing between white asphalt mixtures and can effectively scatter light, thereby improving covering power and ensuring color stability of the road surface.

[0048] Optionally, the petroleum resin is one or more of C9 petroleum resin, C5 petroleum resin or coumarone resin.

[0049] On the other hand, the present application provides a method for preparing a white asphalt mixture for a highway tunnel pavement, the method being used to prepare the above-mentioned white asphalt mixture, the method comprising the following steps:

[0050] (1) Heat the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively according to weight;

[0051] (2) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, fine aggregate and bright asphalt heated in the above step (1) into the preheated container, and stirring at a speed of 45-75 r / min for 50-60 s to obtain a mixture A;

[0052] (3) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0053] (4) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 120-150 min to obtain a white asphalt mixture.

[0054] The present application realizes the preparation of white asphalt mixture for highway tunnel pavement through the above scheme, by first heating the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively, and then stirring and mixing to obtain mixture A, then maintaining the temperature, stirring the mineral powder and composite flame retardant at a speed of 45-75rad / min to obtain mixture B, and finally stirring and mixing mixture A, mixture B and unheated titanium dioxide at a speed of 500-700rad / min to obtain white asphalt mixture. By heating the components of the asphalt mixture separately and then mixing them, the mixing efficiency of each component can be improved. At the same time, the rotation speed when preparing mixture A and mixture B is 45-75rad / min, and the rotation speed after adding titanium dioxide is 500-700rad / min. The difference in shear speed affects the mixing efficiency and interaction between the components of the asphalt mixture, and then affects the synergistic effect between the components, and affects the strength and durability of the asphalt mixture. Increasing the shear rate after adding titanium dioxide can improve the uniform dispersion of titanium dioxide in the asphalt mixture, so that the asphalt mixture has uniform color distribution and gloss when paved on the road surface.

[0055] More preferably, the composite flame retardant provided by the present application also includes magnesium silicate, and the nanoclay is a modified nanoclay obtained by modification with N-hydroxyoctylamide. The preparation method of the modified nanoclay includes: dispersing the nanoclay in anhydrous ethanol at 30-50°C, ultrasonically treating for 30-60s for activation and interlayer peeling to obtain a first dispersion, then adding N-hydroxyoctylamide to the first dispersion, stirring at a speed of 40-60rad / min, and ultrasonically treating for 3-7min, continuing to peel and grafting N-hydroxyoctylamide on the surface and interlayer of the thin layer of nanoclay to obtain a second dispersion, and drying the second dispersion at 40-60°C to constant weight to obtain modified nanoclay. The weight-volume ratio of nanoclay, anhydrous ethanol and N-hydroxyoctanoyl is 1 g: 10-20 mL: 1.1-1.3 g, and the composite flame retardant includes modified nanoclay, ammonium polyphosphate, aluminum hydroxide and magnesium silicate in weight ratios of (50-52): (30-35): (8-10): (0.5-1.2) respectively.

[0056] The nanoclay is modified by N-hydroxyoctanoylamide, which increases the interlayer spacing of the nanoclay, and N-hydroxyoctanoyl is grafted on the surface and interlayer of the thin nanoclay. Compared with nanoclay, the surface area and surface adsorption capacity are increased, and the synergistic effect with ammonium polyphosphate and aluminum hydroxide is enhanced, the flame retardant and smoke suppression performance of the road surface is improved, and the describing properties between the components are improved, so that the dispersion performance of the nanoclay in the asphalt mixture is improved. At the same time, the modification of N-hydroxyoctanoyl forms a three-dimensional network structure between the modified nanoclay and the components in the asphalt mixture, which improves the high temperature stability and bearing capacity of the asphalt mixture, thereby improving the road performance of the asphalt mixture. Magnesium silicate is also adsorbed on the interlayer and surface of the modified nanoclay, further filling the pores between the modified nanoclay and the asphalt, improving the stability of the three-dimensional network structure, thereby improving the integrity of the mixed asphalt pavement, and thereby improving the flame retardant and smoke suppression performance.

[0057] Furthermore, the main component of titanium dioxide is titanium dioxide, and the addition of magnesium silicate can also work synergistically with titanium dioxide to improve the glossiness of white asphalt mixture pavement, thereby extending the service life of the pavement.

[0058] Optionally, the method for preparing bright color asphalt comprises the following steps:

[0059] Mixing and preheating step: taking naphthenic oil, petroleum resin and EVA resin by weight, and stirring and preheating at 160-170°C for 10-25min to obtain a molten mixture, and the stirring speed is 700-1000rad / min;

[0060] SBS modifier and compatibilizer adding step: maintaining the temperature at 160-170° C., adding the SBS modifier and compatibilizer to the molten mixture, and shearing at a speed of 4500-5500 rad / min for 30-35 minutes;

[0061] Anti-aging agent adding step: cooling to 150-160°C, and adding 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in sequence, shearing at a speed of 2000-2500 rad / min for 15-20 minutes to obtain a bright-colored asphalt primary product;

[0062] Development steps: Place the initial bright-colored asphalt product in an oven at 160-165°C for 1.5-2 hours to obtain bright-colored asphalt.

[0063] Specifically, the naphthenic oil, petroleum resin and EVA resin are stirred and preheated at 160-170°C to obtain a molten mixture, which is helpful for EVA resin to modify the naphthenic oil and petroleum resin, and can improve the high-temperature strength and stability of the asphalt mixture, and reduce rutting and permanent deformation. Then, SBS modifier and compatibilizer are added to the molten mixture. The compatibilizer is used to improve the compatibility between the components, which is conducive to the SBS modifier to modify the naphthenic oil and petroleum resin again, improve the adhesion and elasticity of the asphalt mixture, and improve the adhesion and bonding force between the bright asphalt and other component materials, thereby improving the high-temperature stability and anti-stripping performance of the asphalt mixture.

[0064] On the other hand, the present application provides an application of a white asphalt mixture for a highway tunnel pavement in the paving of a highway tunnel pavement, wherein the white asphalt mixture is the above-mentioned white asphalt mixture, or a white asphalt mixture prepared by the above-mentioned method. Paving the white asphalt mixture provided by the present application on the highway tunnel pavement not only improves the reflection intensity of the highway tunnel pavement to light, improves the light environment of the tunnel, and improves the safety of tunnel driving. At the same time, it achieves the purpose of flame retardancy and smoke suppression for the tunnel highway, and more importantly, further improves the high temperature stability and durability of the tunnel highway pavement, and improves the road performance of the pavement. Among them, the paving method can be any method well known to those skilled in the art, and is not limited here.

[0065] The present invention is further described in detail below in conjunction with the examples. However, it should be understood that the examples are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0066] Example 1

[0067] The preparation method of white asphalt mixture for highway tunnel pavement in this embodiment is as follows:

[0068] The method comprises the following steps:

[0069] (1) Preparation of bright asphalt:

[0070] Mixing and preheating steps: take naphthenic oil, petroleum resin and EVA resin by weight, and stir and preheat at 160-170℃ for 10min to obtain a molten mixture, with a stirring speed of 700-1000rad / min; keep the temperature at 160-170℃, add SBS modifier and compatibilizer to the molten mixture, and shear at a speed of 4500-5500rad / min for 30min; cool to 150-160℃, add anti-aging agent, and shear at a speed of 2000-2500rad / min for 15min to obtain a bright asphalt primary product; put the bright asphalt primary product into a 160-165℃ oven for 1.5h to obtain a bright asphalt. The petroleum resin is C9 type petroleum resin.

[0071] The bright color asphalt comprises the following components: 30 parts by weight of naphthenic oil, 62 parts by weight of petroleum resin, 5 parts by weight of EVA resin, 4 parts by weight of SBS modifier, 1 part by weight of compatibilizer and 2 parts by weight of anti-aging agent. The anti-aging agent comprises 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:2:0.2.

[0072] (2) Heat the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively according to weight;

[0073] The coarse aggregate includes: 5-10mm crushed stone and 10-15mm crushed stone in a weight ratio of 40:20.

[0074] The fine aggregate includes: 0-3mm machine-made sand and 3-5mm crushed stone in a weight ratio of 26:5.

[0075] (3) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, fine aggregate and bright asphalt heated in the above step (2) into the preheated container, and stirring at a speed of 45-75 r / min for 50-60 s to obtain a mixture A;

[0076] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0077] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 120 min to obtain a white asphalt mixture.

[0078] The white asphalt mixture includes, by weight: 4 parts by weight of light asphalt, 50 parts by weight of coarse aggregate, 25 parts by weight of fine aggregate, 1 part by weight of titanium dioxide, 2 parts by weight of mineral powder and 2.5 parts by weight of composite flame retardant; the composite flame retardant includes nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 50:30:8 respectively.

[0079] Example 2

[0080] The preparation method of white asphalt mixture for highway tunnel pavement in this embodiment is as follows:

[0081] The method comprises the following steps:

[0082] (1) Preparation of bright asphalt:

[0083] Mixing and preheating steps: take cyclohexane oil, petroleum resin and EVA resin by weight, and stir and preheat at 160-170°C for 20 minutes to obtain a molten mixture, with a stirring speed of 700-1000rad / min; keep the temperature at 160-170°C, add SBS modifier and compatibilizer to the molten mixture, and shear at a speed of 4500-5500rad / min for 32 minutes; cool to 150-160°C, add anti-aging agent, and shear at a speed of 2000-2500rad / min for 17 minutes to obtain a bright asphalt preliminary product; put the bright asphalt preliminary product into a 160-165°C oven for 1.8 hours to obtain a bright asphalt.

[0084] The bright asphalt comprises the following components: 31 parts by weight of naphthenic oil, 64 parts by weight of petroleum resin, 6.5 parts by weight of EVA resin, 18 parts by weight of SBS modifier, 1.2 parts by weight of compatibilizer and 12 parts by weight of anti-aging agent. The anti-aging agent comprises 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:3.5:0.3. The petroleum resin is C9 type petroleum resin.

[0085] (2) Heat the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively according to weight;

[0086] The coarse aggregate includes: 5-10mm crushed stone and 10-15mm crushed stone in a weight ratio of 41:22.

[0087] The fine aggregate includes: 0-3mm machine-made sand and 3-5mm crushed stone in a weight ratio of 27:7.

[0088] (3) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, fine aggregate and bright asphalt heated in the above step (2) into the preheated container, and stirring at a speed of 45-75 r / min for 50-60 s to obtain a mixture A;

[0089] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0090] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 130 min to obtain a white asphalt mixture.

[0091] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 51:32:9 respectively.

[0092] Example 3

[0093] The preparation method of white asphalt mixture for highway tunnel pavement in this embodiment is as follows:

[0094] The method comprises the following steps:

[0095] (1) Preparation of bright asphalt:

[0096] Mixing and preheating steps: take naphthenic oil, petroleum resin and EVA resin by weight, and stir and preheat at 160-170℃ for 25min to obtain a molten mixture, with a stirring speed of 700-1000rad / min; keep the temperature at 160-170℃, add SBS modifier and compatibilizer to the molten mixture, and shear at a speed of 4500-5500rad / min for 35min; cool to 150-160℃, add anti-aging agent, and shear at a speed of 2000-2500rad / min for 20min to obtain a bright asphalt primary product; put the bright asphalt primary product into a 160-165℃ oven for 2h to obtain a bright asphalt. The petroleum resin is C9 type petroleum resin.

[0097] The bright asphalt comprises the following components: 33.3 parts by weight of naphthenic oil, 66.7 parts by weight of petroleum resin, 8 parts by weight of EVA resin, 33 parts by weight of SBS modifier, 1.5 parts by weight of compatibilizer and 22 parts by weight of anti-aging agent. The anti-aging agent comprises 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:5.5:0.4.

[0098] (2) Heat the coarse aggregate, fine aggregate and bright asphalt to 160-170°C respectively according to weight;

[0099] The coarse aggregate includes: 5-10mm crushed stone and 10-15mm crushed stone in a weight ratio of 43:25.

[0100] The fine aggregate includes: 0-3mm machine-made sand and 3-5mm crushed stone in a weight ratio of 29:9.

[0101] (3) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, fine aggregate and bright asphalt heated in the above step (2) into the preheated container, and stirring at a speed of 45-75 r / min for 60 s to obtain a mixture A;

[0102] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0103] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 150 min to obtain a white asphalt mixture.

[0104] The white asphalt mixture includes, by weight: 7 parts by weight of light asphalt, 58 parts by weight of coarse aggregate, 30 parts by weight of fine aggregate, 3 parts by weight of titanium dioxide, 4 parts by weight of mineral powder and 3.5 parts by weight of composite flame retardant; the composite flame retardant includes nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 52:35:10 respectively.

[0105] Comparative Example 1

[0106] The difference from Example 2 is that:

[0107] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 120-150 min to obtain a white asphalt mixture.

[0108] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3.7 parts by weight of composite flame retardant.

[0109] Comparative Example 2

[0110] The difference from Example 2 is that:

[0111] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 120-150 min to obtain a white asphalt mixture.

[0112] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant 2.3.

[0113] Experimental Example 1

[0114] The flame retardant and smoke suppression properties of the white asphalt mixed materials provided in Examples 1 to 3 and Comparative Examples 1 and 2 were tested. The limiting oxygen index (LOI) test was performed in accordance with the standard NB / SH / T 0815-2010 "Oxygen Index Method for Determination of Combustion Performance of Asphalt"; the smoke density test was performed in accordance with the standard GB / T8627-2007 "Smoke Density Test Method for Combustion or Decomposition of Building Materials". Three parallel tests were set up for each test group, and the average value was taken. The test results are shown in Table 1:

[0115] Table 1

[0116] Limiting oxygen index / % Smoke density / % Example 1 28 40 Example 2 29 42 Example 3 28 41 Comparative Example 1 22 43 Comparative Example 2 18 66

[0117] Experimental Example 2

[0118] The road performance of the white asphalt mixed materials provided in Examples 1 to 3 and Comparative Examples 1 and 2 was tested by the method provided in JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction". Three parallel tests were set up for each test group, and the average value was taken. The test results are shown in Table 2:

[0119] Table 2

[0120]

[0121] It can be seen from Table 1 and Table 2 that the white asphalt mixture provided by the present application has excellent flame retardant and smoke suppression performance. At the same time, the dynamic stability can reflect the high temperature stability of the asphalt mixture, the failure strain can reflect the low temperature crack resistance of the asphalt material, and the splitting strength ratio reflects the water stability of the asphalt material. Referring to Table 2, it can be seen that the dynamic stability, failure strain and splitting strength of Examples 1 to 3 are significantly enhanced compared with Comparative Examples 1 and 2, indicating that the white asphalt mixture provided by the present application not only has a good effect in flame retardant and smoke suppression, but also has a significant improvement in the high temperature, low temperature and water stability of the mixed asphalt. And according to Table 1, when the addition amount of the composite flame retardant increases, the limiting oxygen index of the mixed asphalt does not increase accordingly, but the smoke density increases slightly, indicating that the larger the addition amount of the composite flame retardant, the better the flame retardant and smoke suppression effect.

[0122] Example 4

[0123] The difference from Example 2 is that:

[0124] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0125] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 130 min to obtain a white asphalt mixture.

[0126] The preparation method of modified nanoclay includes: dispersing nanoclay in anhydrous ethanol at 30-50°C, ultrasonically treating for 30s for activation and interlayer peeling to obtain a first dispersion, then adding N-hydroxyoctylamide to the first dispersion, stirring at a speed of 40-60rad / min, ultrasonically treating for 3min, continuing to peel and grafting N-hydroxyoctylamide on the surface and interlayer of a thin layer of nanoclay to obtain a second dispersion, and drying the second dispersion at 40-60°C to a constant weight to obtain modified nanoclay. Wherein: the weight-to-volume ratio of nanoclay, anhydrous ethanol, and N-hydroxyoctylamide is 1g:10mL:1.1g.

[0127] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes modified nano clay, ammonium polyphosphate, aluminum hydroxide and magnesium silicate in a weight ratio of 51:32:9:0.5 respectively.

[0128] Example 5

[0129] The difference from Example 2 is that:

[0130] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0131] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 130 min to obtain a white asphalt mixture.

[0132] The preparation method of modified nanoclay includes: dispersing nanoclay in anhydrous ethanol at 30-50°C, ultrasonically treating for 45s for activation and interlayer peeling to obtain a first dispersion, then adding N-hydroxyoctylamide to the first dispersion, stirring at a speed of 40-60rad / min, ultrasonically treating for 5min, continuing to peel and grafting N-hydroxyoctylamide on the surface and interlayer of a thin layer of nanoclay to obtain a second dispersion, and drying the second dispersion at 40-60°C to a constant weight to obtain modified nanoclay. Wherein: the weight-to-volume ratio of nanoclay, anhydrous ethanol, and N-hydroxyoctylamide is 1g:15mL:1.2g.

[0133] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes modified nano clay, ammonium polyphosphate, aluminum hydroxide and magnesium silicate in a weight ratio of 51:32:9:0.9 respectively.

[0134] Example 6

[0135] The difference from Example 2 is that:

[0136] (4) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0137] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 130 min to obtain a white asphalt mixture.

[0138] The preparation method of modified nanoclay includes: dispersing nanoclay in anhydrous ethanol at 30-50°C, ultrasonically treating for 60s for activation and interlayer peeling to obtain a first dispersion, then adding N-hydroxyoctylamide to the first dispersion, stirring at a speed of 40-60rad / min, ultrasonically treating for 7min, continuing to peel and grafting N-hydroxyoctylamide on the surface and interlayer of a thin layer of nanoclay to obtain a second dispersion, and drying the second dispersion at 40-60°C to a constant weight to obtain modified nanoclay. Wherein: the weight-to-volume ratio of nanoclay, anhydrous ethanol, and N-hydroxyoctylamide is 1g:20mL:1.3g.

[0139] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes modified nano clay, ammonium polyphosphate, aluminum hydroxide and magnesium silicate in a weight ratio of 51:32:9:1.2 respectively.

[0140] Comparative Example 3

[0141] The difference from Example 5 is that:

[0142] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes nano clay, ammonium polyphosphate, aluminum hydroxide and magnesium silicate in a weight ratio of 51:32:9:0.9 respectively.

[0143] Comparative Example 4

[0144] The difference from Example 5 is that:

[0145] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, 3 parts by weight of mineral powder and 3 parts by weight of composite flame retardant; the composite flame retardant includes modified nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of 51:32:9 respectively.

[0146] Comparative Example 5

[0147] The difference from Example 5 is that:

[0148] (No composite flame retardant is added to the mixed asphalt)

[0149] (4) According to weight, the mineral powder is stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B;

[0150] (5) Maintaining the temperature at 160-170° C., the mixture A, the mixture B and the unheated titanium dioxide are stirred at a speed of 500-700 rad / min for 130 min to obtain a white asphalt mixture.

[0151] The white asphalt mixture includes, by weight: 67 parts by weight of light asphalt, 54 parts by weight of coarse aggregate, 27 parts by weight of fine aggregate, 2 parts by weight of titanium dioxide, and 3 parts by weight of mineral powder.

[0152] Experimental Example 3

[0153] The flame retardant and smoke suppression properties of the white asphalt mixed materials provided in Examples 4 to 6 and Comparative Examples 3 to 5 were tested. The limiting oxygen index (LOI) test was performed in accordance with the standard NB / SH / T 0815-2010 "Oxygen Index Method for Determination of Combustion Performance of Asphalt"; the smoke density test was performed in accordance with the standard GB / T8627-2007 "Smoke Density Test Method for Combustion or Decomposition of Building Materials". Three parallel tests were set up for each test group, and the average value was taken. The test results are shown in Table 3:

[0154] Table 3

[0155] Limiting oxygen index / % Smoke density / % Example 4 35 28 Example 5 36 28 Example 6 36 30 Comparative Example 3 24 39 Comparative Example 4 25 40 Comparative Example 5 17.5 89

[0156] Experimental Example 4

[0157] The road performance of the white asphalt mixed materials provided in Examples 4 to 6 and Comparative Examples 3 to 5 was tested by the method provided in JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction". Three parallel tests were set for each test group, and the average value was taken. The test results are shown in Table 4:

[0158] Table 4

[0159] Dynamic stability (times / mm) Failure strain (με) Splitting strength ratio (%) Example 4 8642 2785 86.03 Example 5 8056 2838 87.08 Example 6 8879 2744 86.29 Comparative Example 3 7401 2365 82.1 Comparative Example 4 7123 2405 82.9 Comparative Example 5 2804 2196 80.06

[0160] It can be seen from Tables 3 and 4 that the use of N-hydroxyoctanoyl-modified nanoclay and magnesium silicate in the composite flame retardant can further improve the flame retardant and smoke suppression properties of the white asphalt mixture. At the same time, the modified nanoclay and magnesium silicate can play a synergistic role and jointly improve the high temperature stability and bearing capacity of the asphalt mixture, thereby improving the road performance of the asphalt mixture.

[0161] Experimental Example 5

[0162] A direct combustion test was used to further analyze the flame retardant properties of the asphalt mixtures obtained in Example 2, Example 5, and Comparative Examples 3 to 5. The specific method is: considering that asphalt materials are difficult to ignite in the air, a method of gasoline igniting the test piece is adopted. In order to control the test conditions to be consistent, 100-110g of the test piece is taken, and the test piece is placed in an iron plate. Each test piece is sprinkled with 40mL of gasoline. In order to avoid errors caused by gasoline volatilization, the gasoline is immediately ignited after sprinkling until the test piece is extinguished. The flame retardant properties of the white asphalt mixture are analyzed from the two indicators of combustion time and mass loss rate. Three parallel tests are set up for each test group, and the average value is taken. The test results are shown in Table 5:

[0163] Table 5

[0164] Burning time / s Mass loss / % Example 2 232 4.5 Example 5 220 2.6 Comparative Example 3 259 3.6 Comparative Example 4 251 3.2 Comparative Example 5 266 7.3

[0165] The results show that Example 5 has the best flame retardant performance and is significantly improved compared to Example 2. At the same time, the mass loss of the asphalt mixture obtained from Comparative Examples 3 to 5 is greatly reduced. Combined with the data in Table 3, it is shown that the synergistic effect of modified nanoclay and magnesium silicate can effectively improve the flame retardant and smoke suppression properties and road performance of asphalt concrete.

[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A white asphalt mixture for a highway tunnel pavement, characterized in that: The white asphalt mixture comprises, by weight: 4-7 parts by weight of bright asphalt, 50-58 parts by weight of coarse aggregate, 25-30 parts by weight of fine aggregate, 1-3 parts by weight of titanium dioxide, 2-4 parts by weight of mineral powder and 2.5-3.5 parts by weight of composite flame retardant; The composite flame retardant comprises nano clay, ammonium polyphosphate and aluminum hydroxide in a weight ratio of (50-52):(30-35):(8-10) respectively.

2. The white asphalt mixture for highway tunnel pavement according to claim 1, characterized in that: The bright asphalt comprises the following components: 30-33.3 parts by weight of cyclohexane oil, 62-66.7 parts by weight of petroleum resin, 5-8 parts by weight of EVA resin, 4-33 parts by weight of SBS modifier, 1-1.5 parts by weight of compatibilizer and 2-22 parts by weight of anti-aging agent.

3. The white asphalt mixture for highway tunnel pavement according to claim 2, characterized in that: The anti-aging agent comprises 1076 antioxidant, LDHs and tallow amine polyoxyethylene ether in a weight ratio of 1:2-5.5:0.2-0.

4.

4. The white asphalt mixture for highway tunnel pavement according to claim 1, characterized in that: The particle size of the coarse aggregate is classified into 5-10 mm crushed stone and 10-15 mm crushed stone, wherein the weight ratio of 5-10 mm crushed stone to 10-15 mm crushed stone is 40-43:20-25.

5. The white asphalt mixture for highway tunnel pavement according to claim 1, characterized in that: The particle size of the fine aggregate is classified into 0-3 mm machine-made sand and 3-5 mm crushed stone, wherein the weight ratio of 0-3 mm machine-made sand to 3-5 mm crushed stone is 26-29:5-9.

6. The white asphalt mixture for highway tunnel pavement according to claim 1, characterized in that: The titanium dioxide is selected from anatase titanium dioxide and rutile titanium dioxide.

7. The white asphalt mixture for highway tunnel pavement according to claim 2, characterized in that: The petroleum resin is one or more of C9 petroleum resin, C5 petroleum resin or coumarone resin.

8. A method for preparing white asphalt mixture for highway tunnel pavement, characterized in that: The method is used to prepare the white asphalt mixture according to any one of claims 1 to 7, and the method comprises the following steps: (1) heating the coarse aggregate, the fine aggregate, and the bright asphalt to 160-170° C. respectively according to weight; (2) taking a container and preheating the temperature in the container to 160-170° C., adding the coarse aggregate, the fine aggregate and the bright asphalt heated in the above step (1) into the preheated container, and stirring at a speed of 45-75 r / min for 50-60 s to obtain a mixture A; (3) According to weight, the mineral powder and the composite flame retardant are stirred at a speed of 45-75 rad / min and heated to 160-170° C. to obtain a mixture B; (4) maintaining the temperature at 160-170° C., stirring the mixture A, the mixture B and the unheated titanium dioxide at a rotation speed of 500-700 rad / min for 120-150 min to obtain the white asphalt mixture.

9. The method for preparing white asphalt mixture for highway tunnel pavement according to claim 8, characterized in that: The preparation method of the bright color asphalt comprises the following steps: Mixing and preheating step: taking the naphthenic oil, the petroleum resin and the EVA resin by weight, and stirring and preheating at 160-170° C. for 10-25 min to obtain a molten mixture, with a stirring speed of 700-1000 rad / min; SBS modifier and compatibilizer adding step: maintaining the temperature at 160-170° C., adding the SBS modifier and the compatibilizer to the molten mixture, and shearing at a speed of 4500-5500 rad / min for 30-35 min; Anti-aging agent adding step: cooling to 150-160° C., and sequentially adding the 1076 antioxidant, the LDHs and the tallow amine polyoxyethylene ether, and shearing at a speed of 2000-2500 rad / min for 15-20 minutes to obtain a bright-colored asphalt primary product; Development step: Place the bright-colored asphalt product in an oven at 160-165° C. for 1.5-2 hours to obtain bright-colored asphalt.

10. Application of white asphalt mixture for highway tunnel pavement in highway tunnel pavement paving, characterized in that: The white asphalt mixture is the white asphalt mixture according to any one of claims 1 to 7, or the white asphalt mixture prepared by the method of claim 8 or 9.

Citation Information

Patent Citations

  • Synergic flame retardance asphalt material and preparation method thereof

    CN102604396A

  • Environment-friendly material for packaging solar lithium battery and preparation method thereof

    CN110294888A

  • Warm-mixing high-brightness pavement layer material used in tunnel and preparation method thereof

    CN115159897A

  • Tunnel pavement mixture of porous steel slag loaded nano flame retardant and construction method of tunnel pavement mixture

    CN116535137A

  • Composite warm-mixing flame retardant and preparation method thereof

    CN117801363A

Cited By

  • Heat reflection type mixture applied to road surface thin layer, preparation method and application

    CN121717575A